MANAGERIAL OWNERSHIP AND DIVIDEND PAYMENT POLICY (Case Study on Manufacturing Companies Listed on IDX During the Period 2010-2019) - Muhammad Azmi Caesardi; Windijarto Windijarto (JURNAL ILMIAH EDUNOMIKA, 2024)
Dividend catering theory explains that the dividend payment policy is closely related to fulfilling the requests of investors as share owners. When there is an increase in investor demand for dividend payments, the percentage of managers as company representatives in making policies to increase dividend payments will be greater. However, the existence of managers who are also share owners is a problem in itself when paying dividends. This research aims to measure the significance of the influence of managerial ownership, the presence of the manager as the majority shareholder, and the number of shares owned by the manager on dividend payments. The samples in this research were 33 manufacturing companies on the Indonesia Stock Exchange in the 2010-2019 period which were determined using purposive sampling techniques. The data analysis technique used is panel data regression analysis technique. The results of this research state that managerial ownership, the presence of the manager as the majority shareholder, and the number of shares owned by the manager have a significant negative effect on dividend payments